(untitled) (Canadian Perspectives on Academic Integrity, 2021)
Students have been connected digitally from an early age and have been encouraged throughout their educational journey to turn to the internet for information. However, less emphasis is typically placed on educating students about the origin and appropriateness of these sources. For many post-secondary students, it can be challenging to distinguish between resources that are supportive of their academic development and resources that are undermining and questionable in their veracity. In this workshop, we discuss the emergence and infiltration of pay-to-pass websites in the Canadian post-secondary setting. We differentiate pay-to-pass websites from other forms of contract cheating by describing them as sites encouraging students to share and access course material, assignments, tests, and notes for academic and personal gain. These sites are alluring to students because they commonly offer real-time support from academic ’experts’ or tutors that is available 24/7. In the rapid shift to online learning due to the COVID-19 pandemic, we have acutely observed the impact of these services on student behaviour in online-based assessments. This workshop examines the growing scope and deepening impact of these sites on teaching and learning in the post-secondary context. To address the challenges posed by these websites, we present a three-part approach that may be implemented in the efforts to uphold academic integrity in post-secondary education.